The causal relationship between abdominal obesity and lower bone mineral density: A two-sample mendelian randomization study - Wang, Xiang-xuan; Lin, Kai-nan; Xu, Wen-chen; Chen, Hui (Frontiers in Genetics, 2022)
Aims: The purpose of this study was to assess the causal effect of abdominal obesity on bone mineral density by two-sample Mendelian randomization (MR). Methods: Abdominal obesity was chosen as exposure in this study. Single nucleotide polymorphisms, extracted from Genome-wide association analysis (GWAS) data, which are closely associated with waist circumference (WC), hip circumference (HC), and waist-to-hip ratio (WHR) were used as instrumental variables to perform MR studies. Different site bone mineral density, such as total bone mineral density (TBMD) and forearm bone mineral density (FBMD) were chosen as outcomes. Inverse variance weighted (IVW) was used as the primary method to assess this causality. Results: According to the IVW method (β = −0.177; 95% CI = −0.287, −0.067; p = 1.52 × 10–3), WC had a negative causal relationship with TBMD, besides, with one standard deviation (SD) higher in HC, there was a 0.195 SD decrease in TBMD (95% CI = −0.279, −0.110; p = 6.32 × 10–6), and with an increase of one SD in HC was related to a decrease of 0.312 SD in FBMD analyzed by the IVW. Conclusion: This study showed that abdominal obesity has a negative effect on bone mineral density.